Influência dos elementos estanho e zinco nos processos de degradação em um sistema fotocatalítico - Wolf, William Felipe (2022)
The nanostructured semiconductors ZnO and SnO2 have been widely studied due to their unique characteristics that make them viable for several applications. The objective of this work is to verify the evolution, contribution of characteristics, and the degradative efficiency of products formed by nanocomposites of ZnO/SnxOx, Sn-doped ZnO and Zn-doped SnxOx. Structural, morphological, optical, electrical and degradative efficiency were analyzed. The ZnO phase has a hexagonal wurtzite structure and the SnOx (x=1.2) phase has a tetragonal rutile structure, and the band gap energy values range from 2.98 to 3.79 eV for the couple or doped samples. The morphological analysis demonstrated the existence of structures of nanorods, nanobelts, nanofibers, nanonails, plate shape, spherical particles and flower structure. Couple or doping increases photocatalytic efficiency, especially through heterojunction formation, emergence of new entrapment states, generation of defects, increase in conductivity and increase in surface area.